2021
DOI: 10.3390/brainsci11050526
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexic Readers Improve without Training When Using a Computer-Guided Reading Strategy

Abstract: Background: Flawless reading presupposes the ability to simultaneously recognize a sequence of letters, to fixate words at a given location for a given time, to exert eye movements of a given amplitude, and to retrieve phonems rapidly from memory. Poor reading performance may be due to an impairment of at least one of these abilities. Objectives: It was investigated whether reading performance of dyslexic children can be improved by changing the reading strategy without any previous training. Methods: 60 dysle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(62 citation statements)
references
References 101 publications
(217 reference statements)
4
58
0
Order By: Relevance
“…Alternatively, non-dyslexics favor a whole word lexical strategy, which would provide a larger amplitude as the adolescent moves across the whole word [41]. Werth has also found that segmentation of text and longer fixation times improves oculomotor abnormalities [42,43]. It is possible that segmenting the text into smaller portions reduces the need for accommodative effort, and therefore for accommodative vergence, decreasing the stress on the dyslexic child and allowing for more coordinated movements.…”
Section: Cognitive Aspects Of Reading Differencesmentioning
confidence: 99%
“…Alternatively, non-dyslexics favor a whole word lexical strategy, which would provide a larger amplitude as the adolescent moves across the whole word [41]. Werth has also found that segmentation of text and longer fixation times improves oculomotor abnormalities [42,43]. It is possible that segmenting the text into smaller portions reduces the need for accommodative effort, and therefore for accommodative vergence, decreasing the stress on the dyslexic child and allowing for more coordinated movements.…”
Section: Cognitive Aspects Of Reading Differencesmentioning
confidence: 99%
“…When eye movements, fixation times, saccadic amplitude, and speech response latency were guided by a computer, children with dyslexia improved their reading performance drastically without any previous training [59]. In earlier studies, children with dyslexia reduced their reading mistakes by about two-thirds after learning a new reading strategy within less than 30 min [56][57][58]60].…”
Section: Is Dd Due To Impairment Of M-cells?mentioning
confidence: 99%
“…Children who can see words clearly without knowing the phonemes belonging to the sequence of letters that make up the word are by no means typical for children with DD. None of the 356 children in our studies [56][57][58][59][60] suffered from such a phonological impairment but most of them still had a severe DD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations